2013
DOI: 10.1007/s40544-013-0028-9
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and tribological properties of epoxy matrix composites modified with microencapsulated mixture of wax lubricant and multi-walled carbon nanotubes

Abstract: Abstract:The mechanical and tribological properties of epoxy composites modified with microencapsulated wax lubricant and multi-walled carbon nanotubes (MWCNTs) were investigated. The increased soft microcapsules embedded in the epoxy matrices were responsible for the reduced micro-hardness and Young's modulus of the epoxy composites. It was found that the friction of the epoxy composites greatly decreased with increased microcapsule content due to combined lubricating effects of the both wax lubricant and MWC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 34 publications
0
49
1
Order By: Relevance
“…Generally, the mechanical strength of a polymer has a significant influence on its friction coefficient and wear [41,42]. The poor mechanical strength of a polymer can result in the higher friction coefficient of the polymer by promoting the contact between the polymer and its counterpart and the wear of the polymer attributed to micro-plastic deformation and micro-cutting caused by the surface asperities of the counterpart [41,42].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, the mechanical strength of a polymer has a significant influence on its friction coefficient and wear [41,42]. The poor mechanical strength of a polymer can result in the higher friction coefficient of the polymer by promoting the contact between the polymer and its counterpart and the wear of the polymer attributed to micro-plastic deformation and micro-cutting caused by the surface asperities of the counterpart [41,42].…”
Section: Resultsmentioning
confidence: 99%
“…The poor mechanical strength of a polymer can result in the higher friction coefficient of the polymer by promoting the contact between the polymer and its counterpart and the wear of the polymer attributed to micro-plastic deformation and micro-cutting caused by the surface asperities of the counterpart [41,42]. The increased hardness and elastic modulus of the epoxy composites with increased SCF content (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The released ionic liquid from broken microcapsules should form a thin film on the contact surface. This thin film effectively lubricates the rubbing surfaces, lessens the direct solid-solid contact between the steel ball and the composite, reduces the wear of the rubbing surfaces, and lessens the interactions between the rubbing surfaces and wear particles [16,17]. Figure 6c shows the wear widths and depths of the pure polyurethane composite coating and polyurethane composite coating filled with microcapsules.…”
Section: Characterization Of the Microcapsulesmentioning
confidence: 99%
“…To overcome or circumvent the drawbacks of external liquid lubricants, liquid lubricants were encapsulated to fabricate organic or inorganic shell microcapsules, and the microcapsules were further incorporated to polymer matrixes to provide ultra-low friction coefficient and wear rate because of the effective lubricating effect of released lubricant from rupture microcapsules [16,17]. Recently, Khun et al [18] reported that silicone composite coating modified by microencapsulated wax lubricant exhibited considerably lower friction coefficient compared to pure silicone coatings.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, significant microwave features are apparently found in the center of the wear track as shown in Figure 19.7(a) and (b). The repeated sliding of the steel ball under a high normal load causes surface fatigue which in turns initiates minute cracks perpendicular to the sliding direction and propagates the cracks into the subsurface [48][49][50]. The formation of a network of microcracks creates microwave features as found in Figure 19.7(b) [49,50].…”
Section: 6mentioning
confidence: 99%